Identification of characteristic aroma compounds in raw and thermally processed African giant snail (Achatina fulica) - Lasekan, Ola; Muniady, Megala; Mee, Lin; Daba, Fatma (Springer, 2018)
BACKGROUND: Food flavor appreciation is one of the first signals along with food appearance and texture encountered by consumers during eating of food. Also, it is well known that flavor can strongly influence consumer's acceptability judgment. The increase in the consumption of snail meat across the world calls for the need to research into the aroma compounds responsible for the distinctive aroma notes of processed snail meat.